Competency Framework for Podiatric Medicine Training: A Validation Report Based on an Adapted E-Delphi Across Canada - Yassin Andoulsi; Olivier Hue; Martine Brousseau; James Hill; Joel Alleyne; Virginie Blanchette (Journal of Medical Education and Curricular Development, 2024)
OBJECTIVES Competency-based medical education has been introduced into many health professional curricula. Based on CanMEDs, a framework has recently been developed for podiatric medicine education in Canada. This study aimed to validate the framework through a consensus of various podiatric medicine experts across Canada. METHODS An adapted Delphi method was used for content validation. Two structured online questionnaires were used to gather expert opinions and agreement on the roles and core competencies described in the framework previously developed. The validation consensus threshold was set at a minimum of 80% agreement. The summary of comments and suggestions was used to reformulate certain items after the research team reached a consensus. RESULTS Out of the 51 experts invited from the Canadian Podiatric Medicine Association, 19 completed the first-round questionnaire (mean podiatric experience = 24.5 years; standard deviation 17.6). After the first round, “Podiatric Expert”, “Communicator” and “Scholar” roles have been modified. After these modifications, a consensus was obtained at the second round completed by 13 experts. Overall, 95% of the experts agreed that the competency framework was relevant even if some indicators would need to be adapted to suit the requirements of each province and territory. CONCLUSION This validated framework supports the excellence and the quality of our podiatric educational program. It also promotes the adoption of a uniform education of podiatrists in Canada and worldwide.